Prepared Electrical Resistivity Been Pure B TiO a 3 Impurity - Mohmaed, M. Z.; Rmthan, A. A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
3 BaTiO was prepared by mixing the components of 3 BaCO and 2 TiO by ratio [1:1] ØŒ This paper is devoted to study the effect of radition on the electrical properties of 3 BaTiO . Some of prepared samples were exposed to fast neutrons ï€¨ ï€© SMeV and ï€¨ ï€© MeV14 . In addition ØŒ Some samples were exposed to gamma â€“ ray with dosage ï€¨ ï€© Rad81.5 10 ï‚´ . The results showed that the exposition of some samples to fast neutrons  ï€¨ ï€© SMeV and ï€¨ ï€© MeV14 lead to increase the electrical resistivity with the study of the effect of the addition of impurity on electrical resistivity . The addition of two compounds ï€¨ ï€© 2 3Yb O and ï€¨ ï€© 2 3Sm O lead to decrease of electrical resistivity at a concentration of ï€¨ ï€© 0.2 % mol for both compounds ØŒ while the increase of concentration at ï€¨ ï€© 0.5 % mol lead to increase electrical resistivity again .